Evaluation of NCS rapid plasma reagin card test, a new screening kit for syphilis. - Fischer, G S (1989)
Agreements in qualitative and quantitative test results between the recently marketed NCS rapid plasma reagin card test (NCS Diagnostics Corp.) and the Macro-Vue rapid plasma reagin 18-mm circle card test (Hynson, Westcott and Dunning) were 99.2 and 99.1%, respectively, indicating the NCS RPR card test to be an acceptable alternative procedure for the serodiagnosis of syphilis.